Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/mnfr.202100356
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Coffee Consumption and Nonalcoholic Fatty Liver Disease in the South Korean General Population

Abstract: Scope To identify the cross‐sectional and prospective association between coffee consumption and nonalcoholic fatty liver disease (NAFLD) among South Korean adults. Methods and Results Participants are selected from the Health Examinees study. NAFLD is defined using three non‐invasive indexes: fatty liver index (FLI), hepatic steatosis index, and fibrosis‐4 calculator (FIB‐4). In the cross‐sectional analysis, higher habitual coffee consumption is associated with a lower risk for NAFLD, define using the FLI, (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Numerous meta-analyses have consistently reported the beneficial effects of coffee consumption on human health. These benefits include a reduction of oxidative damage (Tan et al 2021;Zheng et al 2022), an increase in telomere length (Cardin et al 2013), and activation proteins involved in cell protection (Wahl et al 2017;Kolb et al 2020;Karabegović et al 2021). Moreover, coffee consumption has been associated with a decrease in inflam-matory responses (Jones et al 2010;Aleksandrova et al 2015;Kolb et al 2020;Tan et al 2021;Zheng et al 2022), and collagen synthesis (Cardin et al 2013;Ebadi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous meta-analyses have consistently reported the beneficial effects of coffee consumption on human health. These benefits include a reduction of oxidative damage (Tan et al 2021;Zheng et al 2022), an increase in telomere length (Cardin et al 2013), and activation proteins involved in cell protection (Wahl et al 2017;Kolb et al 2020;Karabegović et al 2021). Moreover, coffee consumption has been associated with a decrease in inflam-matory responses (Jones et al 2010;Aleksandrova et al 2015;Kolb et al 2020;Tan et al 2021;Zheng et al 2022), and collagen synthesis (Cardin et al 2013;Ebadi et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These benefits include a reduction of oxidative damage (Tan et al 2021;Zheng et al 2022), an increase in telomere length (Cardin et al 2013), and activation proteins involved in cell protection (Wahl et al 2017;Kolb et al 2020;Karabegović et al 2021). Moreover, coffee consumption has been associated with a decrease in inflam-matory responses (Jones et al 2010;Aleksandrova et al 2015;Kolb et al 2020;Tan et al 2021;Zheng et al 2022), and collagen synthesis (Cardin et al 2013;Ebadi et al 2021). The anti-inflammatory and antioxidant properties of coffee consumption may also help reduce the risk of NAFLD, hepatic fibrosis (Ebadi et al 2021;Tan et al 2021), www.journal-dtt.org and hepatocellular carcinoma (Barré et al 2022;Zheng et al 2022), although conflicting results have been reported in some cohort studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood indexes such as fasting blood glucose (FBG), alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transpeptidase (GGT), alkaline phosphatase (ALP), urea nitrogen (UREA), uric acid (UA), creatinine (CREA), total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), homocysteine (HCY), and free triiodothyronine (FT3) were tested in the department of laboratory medicine and nuclear medicine of the Affiliated Hospital of Southwest Medical University. The fatty liver index (FLI) was calculated using the following formulaa: FLI = 1/[1 + exp(−x)] × 100, x = 0.953 × ln (triglycerides) (mg/dl) + 0.139 × BMI (kg/m2) + 0.718 × ln (γ-glutamyl-transferase) (U/L) + 0.053 × WC (cm)–15.745 ( Tan et al, 2021 ). After overnight fasting, the blood samples from all the participants were collected in the separation gel promoting tubes on the morning of the day of ultrasound examination.…”
Section: Methodsmentioning
confidence: 99%